Three-Dimensional Modelling of Desorbed Gas Volume and Comparison to Gas Production Rate in the Montney Plays, Western Canadian Sedimentary Basin. (16th March 2021) - Song, Gihun; Lee, Hyun Suk; Shin, Hyundon
Abstract : Shale reservoir has been focused among unconventional resources since the first extraction of free and adsorbed gas from the low-permeable Barnett Shale via horizontal drilling and hydraulic fracturing. In the beginning of production, free gas was rapidly recovered through an artificial fracture system, and then, desorbed gas followed at the final stage due to a decrease of reservoir pressure. This desorbed gas volume commonly occupies 10 to 40% of total gas production in shale gas play although it shows wide variety in cumulative gas volume and production time. The largest gas production in Canada is recovered from either tight sandstone or shale reservoirs. The Montney play in Western Canadian Sedimentary Basin (WCSB) has produced up to 80% of Canadian natural gas production. The desorbed gas production from this play has been reported up to 10% of total produced gas. The distribution and productivity of the desorbed gas have not been fully studied. Therefore, we focus to understand the distribution of the desorbed gas volume of eastern, middle, and northwestern areas in the Montney play. The desorbed gas volume within these areas was estimated from the relationship among canister, illite, and shale volumes in core samples and well logs. The average shale volume fraction in eastern area is 0.38 v / v, the average illite mineral volume fraction is 0.25 v / v, and the average desorbed gas volume refers to 8.52 scf/ton. In middle area, calculated volume represents 0.34 v / v, 0.216 v / v, and 8.15 scf/ton as listed above. The northwestern area also shows 0.65 v / v, 0.4 v / v, and 9.78 scf/ton, respectively. 3D models of each area indicated relatively rich and lack parts of desorbed gas volume. These estimated desorbed gas volume and gas production history were compared in order to understand when and how the desorbed gas would affect to gas production. It shows strong positive relationship, gradually increasing correlation to the later stage (from 24-44 months to 36-44 months) of gas production in the entire areas. This result implies that the estimation of later stage gas productivity is able from the estimated volume of desorbed gas, and also, the total gas production can be forecast in shale gas reservoir. Northwestern area in Montney play preserves relatively abundant desorbed gas volume, which will be dominant after 24 months of production.